Evaluasi Program Sholat Dhuha Berjama’ah dengan Model Cse-Ucla di Ma Daarul ‘Ulum Tamansari : Penelitian - Sofiah, Sofiah (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This research aims to evaluate the overall implementation of the Congregational Dhuha Prayer program at MA Daarul 'Ulum Tamansari. This evaluation research uses the CSE-UCLA (Center for the Study of Evaluation – University of California in Los Angeles) evaluation model. This research uses a combined approach or Mix Methods (qualitative and quantitative). Data collection uses questionnaires, interviews, observation and documentation methods. As for data analysis, the descriptive analysis method was used. The location of the research was at MA Daarul 'Ulum Tamansari. The results of the research show that: The assessment system in terms of the formal legal basis for the Dhuha Jam'ah Prayer program at MA Daarul 'Ulum Tamansari is felt to be not strong enough; program planning, for work programs, educator profiles, student profiles, class administration and also learning facilities as a whole are still not good; program implementation, from the research results it can be said to be not good overall. Because all the components in the implementation program have not been implemented well; The improvement program from all sides can be said to have functioned well by looking at the relatively high percentage results; The certification program from the data obtained does show good results because the level of student participation in the Congregational Dhuha Prayer program is 80%, however there is no data evidence that states the exact number of students who took part in this activity.